ADAM10 and ADAM17 regulate EGFR, c-Met and TNF RI signalling in liver regeneration and fibrosis - Olga Zbodakova (Nature Portfolio, 2021)
Abstract ADAM10 and ADAM17 are proteases that affect multiple signalling pathways by releasing molecules from the cell surface. As their substrate specificities partially overlaps, we investigated their concurrent role in liver regeneration and fibrosis, using three liver-specific deficient mouse lines: ADAM10- and ADAM17-deficient lines, and a line deficient for both proteases. In the model of partial hepatectomy, double deficient mice exhibited decreased AKT phosphorylation, decreased release of EGFR activating factors and lower shedding of HGF receptor c-Met. Thus, simultaneous ablation of ADAM10 and ADAM17 resulted in inhibited EGFR signalling, while HGF/c-Met signalling pathway was enhanced. In contrast, antagonistic effects of ADAM10 and ADAM17 were observed in the model of chronic CCl4 intoxication. While ADAM10-deficient mice develop more severe fibrosis manifested by high ALT, AST, ALP and higher collagen deposition, combined deficiency of ADAM10 and ADAM17 surprisingly results in comparable degree of liver damage as in control littermates. Therefore, ADAM17 deficiency is not protective in fibrosis development per se, but can ameliorate the damaging effect of ADAM10 deficiency on liver fibrosis development. Furthermore, we show that while ablation of ADAM17 resulted in decreased shedding of TNF RI, ADAM10 deficiency leads to increased levels of soluble TNF RI in serum. In conclusion, hepatocyte-derived ADAM10 and ADAM17 are important regulators of growth receptor signalling and TNF RI release, and pathological roles of these proteases are dependent on the cellular context.